2014
DOI: 10.1111/aor.12328
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis in a Laminar Flow-Through Couette Shearing Device: An Experimental Study

Abstract: Reducing hemolysis has been one of the major goals of rotary blood pump development and in the investigational phase, the capability of hemolysis estimation for areas of elevated shear stresses is valuable. The degree of hemolysis is determined by the amplitude of shear stress and the exposure time, but to date, the exact hemolytic behavior at elevated shear stresses and potential thresholds for subcritical shear exposure remain vague. This study provides experimental hemolysis data for a set of shear stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…More recent work by Boehning et al [37] suggested that increased duration of shear increases the probability of hemolysis, even at lower shear stresses, consistent with earlier work by Offeman & Williams [38]. Thus, our hypothesis of increasing hemolysis with increasing centrifugation forces and times is consistent with earlier observations in different shear environments.…”
Section: Resultssupporting
confidence: 92%
“…More recent work by Boehning et al [37] suggested that increased duration of shear increases the probability of hemolysis, even at lower shear stresses, consistent with earlier work by Offeman & Williams [38]. Thus, our hypothesis of increasing hemolysis with increasing centrifugation forces and times is consistent with earlier observations in different shear environments.…”
Section: Resultssupporting
confidence: 92%
“…4b that the hemolysis rates generally rise from ow setting I to VI, which is associated with increased mean ow rates and higher wall shear stresses (Table 1 and Fig. 7,8,11 To further conrm this, the microscopy images of the red blood cells before and aer being subjected to extracorporeal pumping were examined. This is consistent with previous studies which showed that exposure to shear stresses can lead to red blood cell damage.…”
Section: Hemolysismentioning
confidence: 99%
“…The relationship between shear stress and red blood cell hemolysis (Paul et al,2003, Boehning et al, 2014 or viability loss in hepatocytes (Yasuda et al, 2015) has been noted, although the process of viability loss or cell lysis was not clearly identified. Also, the effects of cell sedimentation and fluid shear stress on cell viability loss were investigated using a microchannel model to imitate the narrow channel of a catheter (Sufiandi et al, 2015).…”
Section: Y © the Japan Society Of Mechanical Engineersmentioning
confidence: 99%